Efficacy of Carbendazim and other Synthetic Fungicides on Taro Leaf Blight Disease caused by Phythophtora Colocasiae (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The results of the serial concentrations of different synthetic fungicides, phytopathogenic fungi and their interactions on isolates from cocoyam had significant effects (P≤0.05) on the percentage inhibition and mycelia growth. P. colocasiae (12.50 mm) treated with hexaconazole had the lowest mycelia growth rate followed by Botryodiplodia theobromea (21.28 mm) with fludioxonil and carbendazim (24.03 mm) while Rhizopus spp (85.83 mm) and F. solani (78.798 mm) on metaxyl recorded the highest mycelia growth. The effects of different environmental stress, fungi and their interaction on mycelia growth showed significant difference on the organisms, the stress and their interactions. No mycelia growth were seen when B. theobromea were subjected to H2O2 (5.00 mm), followed by P.colocasia (14.67 mm). In conclusion, fungicides found to be effective for the control of cocoyam leaf blight in order of merit were carbendazim, fludioxonil, hexaconazole and mancozeb. Metaxyl recorded no or little effect on the inhibition of mycelia growth of all the four fungi organisms isolated from cocoyam as the organisms have developed resistance to it. It should be used in mixture with other fungicides with different mode of actions for example mancozeb.
Keywords: Cocoyam leaf blight; Fungicides; Mycelia growth and resistance